Reorganização cortical pós lesão medular: estudo da conectividade funcional por meio de ressonância magnética funcional - Almeida, Mainda Quintela da Silva Araújo de (2022)
Spinal Cord Injury (SCI) affects the pathways that carry information to and from the brain. After the injury, cerebral plasticity leads to a cortical reorganization, whose consequences on brain functionalities remain unclear. Understanding the effects of the cortical reorganization following SCI is important because of its potential in predicting clinical outcomes, as well as lead to new therapeutic approaches to enhance patient rehabilitation. Our study assessed the functional connectivity (FC) to demonstrate the effects of plasticity on the cortical reorganization after SCI. Functional Connectivity can be defined as statistical dependencies, such as correlation, among measurements of neurophysiological events. We hypothesize that the lesion would alter the connectivity, and the detection of these changes would allow a better understanding of how the flow of information between the areas involved in the sensory-motor dynamics is altered after the injury. Consequently, the cortical alterations that occur after the spinal cord injury due to neuroplasticity would be better understood, enabling better rehabilitation procedures and improved brain-machine interfaces. We studied the FC in 9 SCI subjects and 10 healthy non-SCI control. All participants underwent structural and functional MRI on a 1.5-T magnetic resonance system while executing specific motor-related tasks. Functional connectivity (FC) analysis was performed using SEED-to-Voxel correlation. The supplementary motor area and the precentral and postcentral gyri were chosen as references to the FC evaluation, for they are directly responsible for motor planning, execution, and control. The results demonstrated that SCI triggers a series of neuroplastic changes, especially in the motor and somatosensory cortexes, both in the strength of the connection and in the number of functionally connected brain regions. Following SCI and over the time of the injury, there was a reduction in connections within the somatosensory network and functional connectivity varied according to the task performed by the individual and the SEED region considered. There was a topographic reorganization towards a weakening of the sensorimotor network in subjects with SCI, when compared to subjects in the control group, with decreased proprioception, autonomic and motor control, in addition to reduced association, integration and sensory processing. It was also noted a possible functional reorganization towards the preservation of the motor planning network.